Hypernatremic Dehydration in Term and Preterm Neonates - Kamyar Kamrani; Zahra Sanaei; Nahideh Khosroshahi; Samira Rajabi Eslami; Jalaloddin Amiri (پزشکی بالینی ابن سینا, 2015)
Introduction & Objective: Hypernatremia is associated with serious complications in infants. Given the high morbidity and mortality of neonatal hypernatremia, and since some complica-tions can be prevented, this study was aimed to examine the prevalence of hypernatremia in hospitalized infants and related risk factors. Materials & Methods: This cross-sectional study was performed on 1923 neonates hospitalized in Bahrami Hospital affiliated to Tehran University from October 2011 to October 2012. Demographic data , ward ,gender ,mode of feeding ,gravidity, admission season and method of delivery related to the infants were recorded. For infants with a serum sodium above 150 meq/lit, additional information were collected, including serum urea level, gestational age, date of birth, birth weight, admission weight, head circumference and clinical symptoms. Fi-nally, the data were analyzed using the SPSS software. Results: 74 out of 1923 neonates had serum sodium above 150 meq per liter, which their mean Na was significantly associated with their age groups (P=0.04) and weight loss (P=0.008). Furthermore, the mean of urea in these neonates was significantly related to weight loss (P<0.001). The prevalence of hypenatremia in the hospitalized neonates was 5.2% in autumn, 4.9% in winter, 1.8% in spring and 3.4% in summer.Conclusion: The common symptoms of hypernatremia, icterus and weight loss often cannot be evaluated due to late referral (> a few days after birth) or to the non-exact weight at the birth time (risk factors). The study results confirmed that weighing the neonates at 72 to 96 hours after birth can prevent hypernatremia in infants.